2022
DOI: 10.3389/fbioe.2022.1053679
|View full text |Cite
|
Sign up to set email alerts
|

hMSC exosomes as a novel treatment for female sensitive skin: An in vivo study

Abstract: Background: Recent studies have reported that the incidence of sensitive skin is increasing. Skin sensitivity and skin barrier functions were related to many skin diseases including atopic dermatitis, psoriasis, rosacea, and so on. Mesenchymal stem cell (MSC)-derived exosomes (hMSC) might be considered as a new effective therapeutic scheme.Aims: This study aims to investigate the safety and efficacy of hMSC exosomes as a novel topical treatment for sensitive skin.Patients/Methods: Exosomes were extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In the discussion of cosmesis improvement, Ye et al found that exosome treatment improved sensitive skin scoring of roughness, scaling, erythema, as well as burning, tension, itching, and dryness, as assessed by 1 professional dermatologist on an objective and subjective sensitive skin index. 16 Proffer et al found that exosome treatment produced improvements in facial aging, such as erythema, color evenness, luminosity, wrinkling, and firmness, as measured by computer analysis of photo documentation. 15 Both of these studies excluded anyone who had prior dermatologic or cosmetic procedures, excluding a large population that would potentially be interested in this type of product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the discussion of cosmesis improvement, Ye et al found that exosome treatment improved sensitive skin scoring of roughness, scaling, erythema, as well as burning, tension, itching, and dryness, as assessed by 1 professional dermatologist on an objective and subjective sensitive skin index. 16 Proffer et al found that exosome treatment produced improvements in facial aging, such as erythema, color evenness, luminosity, wrinkling, and firmness, as measured by computer analysis of photo documentation. 15 Both of these studies excluded anyone who had prior dermatologic or cosmetic procedures, excluding a large population that would potentially be interested in this type of product.…”
Section: Resultsmentioning
confidence: 99%
“…Current studies, such as those included in this systematic literature review, focused on skin outcomes over a period of weeks. 16-25 There are currently no studies assessing the long-term implications of topical exosome products.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the evaluated publications describe the topical application of EVs for the treatment of dermatologic conditions. The first study, conducted in China, enrolled 22 female subjects with sensitive skin to be treated with EVs released by primary human MSCs (study n.31, Table 1 ) (Ye et al., 2022 ). Skin sensitivity, including atopic dermatitis and rosacea, is a condition of subjective cutaneous hyper‐reactivity to environmental factors such as cold, heat, and wind (Berardesca et al., 2013 ); its mean prevalence among Chinese women reaches 15%, detrimentally influencing life quality of millions of individuals (Xu et al., 2013 ).…”
Section: Hyper‐inflammatory Conditionsmentioning
confidence: 99%
“…Skin sensitivity, including atopic dermatitis and rosacea, is a condition of subjective cutaneous hyper‐reactivity to environmental factors such as cold, heat, and wind (Berardesca et al., 2013 ); its mean prevalence among Chinese women reaches 15%, detrimentally influencing life quality of millions of individuals (Xu et al., 2013 ). MSC‐EVs were reported to improve scores of objective symptoms (e.g., roughness and erythema), and subjective symptoms, such as tension, burning, or itching, upon treatment (Ye et al., 2022 ). Other two of those studies were performed in Korea and aimed at treating individuals with facial redness subsequent to a specific biological treatment for atopic dermatitis (Dupilumab).…”
Section: Hyper‐inflammatory Conditionsmentioning
confidence: 99%
“…Finally, UCMSC‐exo can reduce skin sensitivity and restore skin barrier function. In clinical use, it ameliorates roughness, erythema, tension, burning, and itching in patients with skin sensitivity, and treats melasma 104,105 …”
Section: The Effects and Mechanism Of Ucmsc Secretome On Skin Rejuven...mentioning
confidence: 99%